DEVELOPMENT OF CONTEXTUAL STUDENT WORKSHEET ON SYSTEM OF LINEAR EQUATION INTEGRATED WITH QUR’ANIC VALUES USING THE ADDIE MODEL FOR GRADE VIII STUDENTS - Soffi Widyanesti Priwantoro; Arilia Triyoga; Syariful Fahmi (IAIN Ambon, 2026)
This study aimed to develop a contextual student worksheet integrated with Qur’anic values in the system of linear equations in two variables. The study evaluated the worksheet’s feasibility, the suitability of Qur’anic values, and described students’ perceptions of the contextual material. This research used the ADDIE model of research and development. Research instruments were adapted from previous studies and reviewed by experts before use. The research subjects were eighth-grade students at MBS Pleret. The developed worksheet included five activities that integrating Qur’anic values. Expert validation using using Ideal Assessment Criteria found the worksheet feasible. The material expert’s average score was 161, in the good category. The media expert’s average score was 144.5, in the very good category. Implementation in small classes with 10 students and large classes with 29 students received student responses of 113,5 and 121, categorized as good and very good. Additionally, the assessment of Qur’anic value suitability in the material scored 24.5 and 20.4 indicating a good category. Students responded positively to the contextual worksheet integrated with Qur’an value, with perceived understanding scores of 35.9 and 36.9, both falling within the good category. These findings, indicates that the developed worksheet is feasible and has the potential to support mathematics learning through contextual activities integrated with Qur’anic values. Keywords: Student worksheet; Qur’anic Values; System of Linear Equation; Contextual